2022
DOI: 10.1017/ipm.2022.41
|View full text |Cite
|
Sign up to set email alerts
|

Spanish validation of the Stigma of Occupational Stress Scale for Doctors (SOSS-D) and factors associated with physician burnout

Abstract: Objectives: The aim of this study was to investigate the psychometric properties of the Spanish version of the Stigma of Occupational Stress Scale for Doctors (SOSS-D) and the factors associated with Physician Burnout in Paraguay. Methods: Participants included 747 Paraguayan healthcare workers, aged 24–77 years old, of both sexes. SOSS-D was translated into Spanish and validated through an exploratory and confirmatory factor analysis. Participants were also scored with the Oldenburg Bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The mental health and well-being of HCWs was the top request for each session evaluation; mental health and well-being for the general patient population was the second most common request in all session evaluations. While the literature on mental health among HCWs in Paraguay is limited, initial evidence suggests relatively high rates of burnout, posttraumatic stress disorder (PTSD), depression, and anxiety symptoms among this population (Villalba-Arias et al, 2020; Villalba-Arias, et al, 2023; Torales et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The mental health and well-being of HCWs was the top request for each session evaluation; mental health and well-being for the general patient population was the second most common request in all session evaluations. While the literature on mental health among HCWs in Paraguay is limited, initial evidence suggests relatively high rates of burnout, posttraumatic stress disorder (PTSD), depression, and anxiety symptoms among this population (Villalba-Arias et al, 2020; Villalba-Arias, et al, 2023; Torales et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, internalized occupational stigma also harms the professional behaviors of practitioners. For instance, internalized occupational stigma significantly positively correlates with uncivilized behaviors, organizational deviance and disapproval, and turnover intention in the workplace [17][18][19][20][21]. Of particular concern is that the tour guide majored undergraduates elicit negative evaluations, such as unstable income and low respect, towards tour guides [22].…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has negatively impacted mental health worldwide (Torales, O’Higgins, et al, 2020). In Paraguay, several studies have reported that the COVID-19 pandemic has caused an increase in perceived stress, irritability, fear, phobia, anxiety, depression, sleep disorders and addictive behaviours in the population, as well as burnout among health care professionals (Barrios et al, 2021, 2022; Ferreira Gould et al, 2021; Figueredo et al, 2022; Torales, Ríos-González, et al, 2020; Torales et al, 2021; Torales, González, et al, 2022; Torales, Ríos-González, et al, 2022). However, research has not measured the level of protective factors for mental health in the general population after the declared end of pandemic by the World Health Organization in the beginning of 2023 (WHO, 2023).…”
Section: Introductionmentioning
confidence: 99%